Topokaryotyping demonstrates single cell variability and stress dependent variations in nuclear envelope associated domains - Jurisic, Anamarija; Robin, Chloé; Tarlykov, Pavel; Siggens, Lee; Schoell, Brigitte; Jauch, Anna; Ekwall, Karl; Sørensen, Claus Storgaard; Lipinski, Marc; Shoaib, Muhammad; Ogryzko, Vasily (Nucleic acids research, 2018)
Abstract. Analysis of large-scale interphase genome positioning with reference to a nuclear landmark has recently been studied using sequencing-based single ce